Penafsiran Al-Qur’an Perspektif Gus Dur dalam Buku Islam Ku, Islam Anda, Islam Kita - Syafri Fajarwanto (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2022)
The interpretation of the modern-contemporary period focuses its interpretation on efforts to position the Qur'an as a book of guidance for humans, namely by prioritizing the